Multiscale Geomechanical Behavior of Fiber-Reinforced Cementitious Composites Under Cyclic Loading Conditions—A Review - McLean, Javaugh; Cui, Liang (Frontiers in Materials, 2021)
As construction materials, cementitious composites such as cemented paste backfill (CPB), cemented soil, and concrete may be subjected to extreme dynamic loadings including impact, blast, and/or seismic loads during their service life. To improve mechanical performance under dynamic loadings, fiber reinforcement technique has been considered a promising approach and extensively used in practice. In this manuscript, a new perspective on the multiscale geomechanical behavior of fiber-reinforced cementitious composites (FRCC) is provided through a comprehensive review on the macroscale constitutive behavior and the associated mechanical properties, and microscale failure processes under cyclic tensile, shear, and compressive loading conditions. For the macroscale mechanical response, this review includes a detailed analysis of the state-of-the-art research in stress-strain behaviors including pre- and post-peak response and hysteretic behaviors. Moreover, the effects of pore water pressure on the dynamic response of soft FRCCs such as CPB are discussed. Furthermore, the link between microscale crack propagation (including the formation of the interfacial transition zone and fracture process zone) and damage accumulation is established for each type of cyclic loading condition. In addition, a critical discussion on the future development of fiber reinforcement is conducted as well. Therefore, this review not only offers guidance and references to the experimental investigation on the multiscale behavior of FRCCs under cyclic loadings, but also promotes the further development of fiber reinforcement techniques.